Option Valuation of Claims on Real Assets: The Case of Offshore Petroleum Leases - Paddock, James L.; Siegel, Daniel R.; Smith, James L. (Quarterly Journal of Economics, 1988)
This paper extends financial option theory by developing a methodology for the valuation of claims on a real asset: an offshore petroleum lease. Several theoretical and practical problems, not present in applying option pricing theory to financial assets, are addressed. Most importantly, we show the necessity of combining option pricing techniques with a model of equilibrium in the market for the underlying asset (petroleum reserves). The advantages of this approach over conventional discounted cash flow techniques are emphasized. The methodological development provides important insights for both company behavior and government policy. Promising empirical results are reported.